Governance for disaster risk reduction: exploring emotional distress and resilience in adolescent affected by flood in Kelantan and the development of peer support group for trauma module - Husain, Maruzairi (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2017)
Background: Natural disaster such as flooding can lead to a com bi nation of physical, health and psychological trauma in both adults and children. This study was conducted to assess the factors associated with psychological trauma among school children affected by flooding which occurred in Kelantan in 2014. Methods: A validation study of the Malay version of Sense of Coherent (SOC-M) and Trauma Screening Questionnaire (TSQ-M) was conducted in the first phase. In the second phase, a cross-sectional study was conducted among school children using SOC-M and TSQ-M as well as a questionnaire for socio-demographic, flood experiences and consequences. Statistical Package for the Social Sciences (SPSS) version 22 was used to perform data analysis using descriptive, independent t test, Pearson correlation and linear regression analysis. Results: From 160 participants, 86 (53.8%) were male and 74 (46.3%) were female. The mean score of TSQ·M was 2.81 (S0=1. 70) and for SOC-M was 48.58 (S0=9.02). Four factors were found to be associated with trauma score, including female gender (p=0.047), moving from home during the flooding (p= 0.013), having difficulty after the flood in relation to schooling and living (p=0.024) and the place to stay after the flood regards to home and property damage (p=0.005). There was a negative correlation between TSQ-M score and SOC (r=· 0.23, p=0.003). Further analysis using multiple linear regression found that moving from house (p=0.016), places to stay after the flood (p=0.009) and SOC-M (p=0.002) were significantly associated with trauma score. In conclusion, the findings of this study were comparable with other studies in other countries.